2021
DOI: 10.31014/aior.1992.04.01.324
|View full text |Cite
|
Sign up to set email alerts
|

Investment Decisions: The Results of Knowledge, Income, and Self-Control

Abstract: Investment is an economic activity that can be a way for a person to expand or maintain his wealth. However, in investing, the public must be more careful in making decisions so that they are not trapped by fake investments. In investing, there are several factors that influence the decision to invest, namely Financial Knowledge, Income, Self-Control, Financial Behavior, and Financial Attitude towards Investment Decisions. This study aims to examine the influence of the variables of Financial Knowledge, Income… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…Previous research revealed a strong association among financial knowledge, financial behavior, and financial wellness (Adiputra, 2021), (Stella et al, 2020), (Choudhary & Kamboj, 2017), (Gaisina & Kaidarova, 2017), (Kamakia et al, 2017), and (Potrich et al, 2016). Financial knowledge helps to make profitable financial decisions, effective use of financial products and services, improve financial behaviors towards sustainable economic growth and happiness (Atmaningrum et al, 2021), (OECD, 2020), (Nguyen et al, 2017), (Aren & Aydemir, 2014). Training, capacity buildings, and exposures mainly in financial products and services increase financial knowledge.…”
Section: Financial Knowledgementioning
confidence: 97%
“…Previous research revealed a strong association among financial knowledge, financial behavior, and financial wellness (Adiputra, 2021), (Stella et al, 2020), (Choudhary & Kamboj, 2017), (Gaisina & Kaidarova, 2017), (Kamakia et al, 2017), and (Potrich et al, 2016). Financial knowledge helps to make profitable financial decisions, effective use of financial products and services, improve financial behaviors towards sustainable economic growth and happiness (Atmaningrum et al, 2021), (OECD, 2020), (Nguyen et al, 2017), (Aren & Aydemir, 2014). Training, capacity buildings, and exposures mainly in financial products and services increase financial knowledge.…”
Section: Financial Knowledgementioning
confidence: 97%
“…Menurut Ademola et al (2019), Pengetahuan Keuangan mengacu pada kepahaman atas dasar konsep keuangan akan bagaimana performa bisnis dan kondisi bisnis diukur menggunakan model mental untuk memfasilitasi, mendukung atau memperkaya pengambilan keputusan. Atmaningrum et al (2021) menunjukkan bahwa variabel pengetahuan keuangan memiliki hasil yang positif terhadap keputusan investasi. Hasil ini mendukung teori perilaku keuangan yaitu jika seseorang yang memiliki pengetahuan lebih mengenai keuangan maka akan lebih bertanggung jawab dalam manajemen dan penyelesaian masalah saat proses pengambilan keputusan investasi.…”
Section: Pengetahuan Keuangan Memiliki Pengaruh Terhadap Keputusan In...unclassified
“…H5: Gender has a significant effect on Investment Decisions Income and Investment Decision According to Dea (2017) in Putri & Hamidi (2019) income is the result obtained for the sacrifices made by someone in the form of material so that their needs are fulfilled, with this income, decision making will be easier by diverting some of their income to invest. The level of income owned by individuals has a role in investment planning where it is adjusted to their income (Atmaningrum et al, 2021). From this statement, it can be said that individuals with higher incomes tend to invest in larger amounts and have more opportunities than individuals with lower incomes.…”
Section: Gender and Investment Decisionmentioning
confidence: 99%
“…Whether individuals with small or large incomes, investment is necessary for every individual. Regardless of the level of individual income without being accompanied by knowledge and good financial management, financial well-being will be difficult to achieve (Atmaningrum et al, 2021)…”
Section: Introductionmentioning
confidence: 99%